Using satellite images to identify heat islands in city of Ilha Solteira – SP - Nishigima, Lucas Barbosa; Silva , Helio Ricardo (Seven Editora, 2023)
With population growth, it is necessary to increase the number of constructions, such as residences, asphalt. With that comes the consequences, because when we have agglomerations of houses there is a lot of absorption of solar rays causing the Urban Heat Islands (ICU) that tend to cause thermal discomfort for the population since there is an increase in temperature in that place. Remote Sensing comes as a solution to identify where the Heat Islands are and with that, we can plan ways to reduce them. This phenomenon was studied in this present work using LandSat-8 satellite images from the years 2018, 2019, 2020 and 2021 in the thermal infrared region (TIRS/LandSat-8) using the free software QGis 3.16 to process the images and determine the temperature of surface, climatological studies were also carried out to find out if there was influence on the formation of Urban Heat Islands in the city of Ilha Solteira. In general, the years 2018 and 2019 were the years with the highest incidence of Heat Islands. DOI:https://doi.org/10.56238/interdiinovationscrese-070